EFFECT OF DRYING TEMPERATURE ON THE QUALITY OF SKIPJACK TUNA KATSUOBUSHI(Katsuwonus pelamis) - Elisa sakinah; Sukirno Mus; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aim of the study was to determine the different temperature of drying process on the quality skipjack tuna katsuobushi(Katsuwonus pelamis). The method used was experimental, composed as CRD, andevaluated for the characteristic of it’s sensory(appearance, aroma, taste and texture), microbiological (TPC and fungal identification), and chemical values ( the content of water, ash, phenol and pH value). The drying process was using the oven set on the temperature at 40-50oC, 65-75oC and 90-100oC.The results showed that the different drying temperature was affected significantly to the value of appearance, taste, texture, phenol content, moisture content and TPC value on the skipjackkatsuobushi. The best quality of skipjack tuna was produced by drying the fish by using oven at the temperature of 40-50oC. It was indicated by the highest value of taste value at 7.7, aroma at 7.4, appearance at 7.3, and texture at 7.4. The best product had the moisture content 11.56 %, ash content 12.79%, pH 7.91, total phenol content 2.82 ppm, TPC 7.2 x 102coloni/gramand the molds identified grown in all products were Aspergillus sp. Keywords: Drying, Katsuobushi, Skipjack Tuna, Temperature.